Modelling Electron Beam Induced Current in III-Nitride Light Emitting Diodes - Utsch, Benjamin; Römer, Friedhard; Faber, Samuel; Bertram, F.; Schmidt, G.; Veit, P.; Berger, C.; Dadgar, A.; Strittmatter, A.; Christen, J.; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2025)
Electron beam induced current (EBIC) has been used as a tool in semiconductor analytics to determine the diffusion length of minority carriers in pn-junctions. Recent progess in controlling the electron beam and penetration has enabled the resolution of much finer structures, including the active region of multi quantum well (MQW) optoelectronic devices. The interpretation of the measured EBIC profiles is not straight forward, though. In this context we have devised and implemented an EBIC model and have simulated the EBIC in an indium gallium nitride (InGaN) MQW light emitting diode. The simulations demonstrate a combined effect of doping, band edges, and the polarization field on the EBIC. The simulations facilitate an isolation of these effects and therefore support the interpretation of the measured EBIC profiles. We demonstrate that the joint experimental and numerical EBIC analysis has the potential to reveal the structure of the III-nitride MQW active region.
CRIS-Team Scopus Importer:2025-11-28